Hormonal and metabolic regulation of tomato fruit sink activity and yield under salinity - Albacete, Alfonso; Cantero-Navarro, Elena; Balibrea, María E; Großkinsky, Dominik K; de la Cruz González, María; Martínez-Andújar, Cristina; Smigocki, Ann C; Roitsch, Thomas; Pérez-Alfocea, Francisco (Journal of experimental botany, 2014)
Salinization of water and soil has a negative impact on tomato (Solanum lycopersicum L.) productivity by reducing growth of sink organs and by inducing senescence in source leaves. It has been hypothesized that yield stability implies the maintenance or increase of sink activity in the reproductive structures, thus contributing to the transport of assimilates from the source leaves through changes in sucrolytic enzymes and their regulation by phytohormones. In this study, classical and functional physiological approaches have been integrated to study the influence of metabolic and hormonal factors on tomato fruit sink activity, growth, and yield: (i) exogenous hormones were applied to plants, and (ii) transgenic plants overexpressing the cell wall invertase (cwInv) gene CIN1 in the fruits and de novo cytokinin (CK) biosynthesis gene IPT in the roots were constructed. Although salinity reduces fruit growth, sink activity, and trans-zeatin (tZ) concentrations, it increases the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) during the actively growing period (25 days after anthesis). Indeed, exogenous application of the CK analogue kinetin to salinized actively growing fruits recovered sucrolytic activities (mainly cwInv and sucrose synthase), sink strength, and fruit weight, whereas the ethylene-releasing compound ethephon had a negative effect in equivalent non-stressed fruits. Fruit yield was increased by both the constitutive expression of CIN1 in the fruits (up to 4-fold) or IPT in the root (up to 30%), owing to an increase in the fruit number (lower flower abortion) and in fruit weight. This is possibly related to a recovery of sink activity in reproductive tissues due to both (i) increase in sucrolytic activities (cwInv, sucrose synthase, and vacuolar and cytoplasmic invertases) and tZ concentration, and (ii) a decrease in the ACC levels and the activity of the invertase inhibitor. This study provides new functional evidences about the role of metabolic and hormonal inter-regulation of local sink processes in controlling tomato fruit sink activity, growth, and yield under salinity.
Keywords: biomasa; exprese genu; Gene Expression; beta-Fructofuranosidase; Abscisic Acid; Biomass; Sodium Chloride; Cell wall invertase; cytokinins; Plant Roots; regulátory růstu rostlin; Carbon Sequestration; květy; tomato.; Plant Proteins; Salinity; chlorid sodný; Cytokinins; Solanum lycopersicum; kořeny rostlin; salinita; cytokininy; Plants, Genetically Modified; buněčná stěna; ovoce; sekvestrace uhlíku; Cell Wall; Flowers; Plant Growth Regulators; sink activity; geneticky modifikované rostliny; fruit; sacharosa; Fruit; salinity; Sucrose; kyselina abscisová; invertasa; rostlinné proteiny